2018
DOI: 10.1111/jep.12903
|View full text |Cite
|
Sign up to set email alerts
|

Impact of educational outreach intervention on enhancing health care providers' knowledge about statin therapy prescribing in Malaysian patients with type 2 diabetes mellitus

Abstract: This work demonstrated the impact of an educational outreach intervention on improving health care providers' knowledge and beliefs about statin therapy. This type of intervention is considered effective for short-term knowledge enhancement. Further research is needed to test the long-term efficacy of such intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“… 31 Furthermore, providing continuing education and designing educational outreach programs to increase prescribers’ knowledge and awareness of the benefit of statin therapy. 32 In addition, to improve prescribers’ adherence to guidelines, the START/STOP criteria (a screening tool used to optimize medication therapy in the elderly) added Statin therapy for the primary prevention of cardiovascular disease in diabetes mellitus as part of the Alert to Right Treatment (START) which should be utilized in patients medication management. 33 …”
Section: Discussionmentioning
confidence: 99%
“… 31 Furthermore, providing continuing education and designing educational outreach programs to increase prescribers’ knowledge and awareness of the benefit of statin therapy. 32 In addition, to improve prescribers’ adherence to guidelines, the START/STOP criteria (a screening tool used to optimize medication therapy in the elderly) added Statin therapy for the primary prevention of cardiovascular disease in diabetes mellitus as part of the Alert to Right Treatment (START) which should be utilized in patients medication management. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Educational outreach visits have also been found to significantly impact clinicians' behavior 28,29 . One study found that clinicians felt educational outreach visits to be the most valuable implementation strategy, as having experts visit clinicians in their own practice setting saved clinicians' time 30 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the physician’s experience with statin-associated muscle symptoms, the combination lipid-lowering therapy, and the indications for non-statin therapy. We have published a detailed schematic diagram of the program components and the survey used in this program [22].…”
Section: Methodsmentioning
confidence: 99%